PENERAPAN TINDAKAN PROGRESSIVE MUSCLE RELAXATION (PMR) DAN DEEP BREATHING EXERCISES (DBE) UNTUK MENGATASI SESAK NAPAS PADA PASIEN PENYAKIT PARU OBSTRUKTIF KRONIS (PPOK) DI RSUP PERSAHABATAN JAKARTA TIMUR - Yanti Silaban, Nataria; Rayasari , Fitrian; Anggraini, Dewi; Sofiani, Yani; Santosa, Puji Raharja (Jurnal Ilmiah Keperawatan IMELDA, 2024)
Background: Chronic obstructive pulmonary disease (COPD) is a chronic lung disease with progressive, irreversible and partially reversible airway obstruction. COPD includes chronic bronchitis and emphysema, or a combination. COPD patients generally complain of continuous shortness of breath and this will result in a decrease in the patient's quality of life and as a result the patient will go back and forth to the hospital. To prevent this, it is necessary to do breathing exercises. The aim of implementing EBNP is to implement Progressive Muscle Relaxation (PMR) and Deep Breathing Exercises (DBE) interventions to change the shortness of breath response in COPD patients in the form of a randomized controlled trial with a pre-post-test design. The sampling technique uses G-Power version 3.1.9.7 with T-test, one tail, effect size 0.53, alpha error 0.05, and power 0.80, a minimum of 18 is required plus a possibility of error of 10%, so the number of patients needed in this study is 20 at Persahabatan Hospital, East Jakarta. The implementation of PMR actions with 13 (thirteen) movements and DBE with 6 (six) movements is carried out every day for 5 weeks, from May 15 to June 16 2023. Method: The study design in this research is a case study involving 40 respondents. Respondents were divided into two groups, namely 20 people in the PMR group and 20 people in the DBE group. Evaluation is carried out every week using the dyspnoe-12 instrument. Results: This application shows that there is a difference in the response to shortness of breath between before and after the PMR procedure (P value 0.001) and the DBE procedure (P value = 0.001). Conclusion: The application of EBNP recommends the need for nurses to carry out PMR and DBE interventions to change the shortness of breath response in COPD patients.